Particle swarm optimisation classical and quantum perspectives - Sun, Jun, 1971-; Lai, Choi-Hong.; Wu, Xiao-Jun. (Boca Raton [Fla.] : CRC Press, 2012)
"This volume provides a detailed description of the state of the art of particle swarm optimization (PSO) and quantum-behaved particle swarm optimization (QPSO) algorithms. The authors present the motivation, principles, and theoretical analysis of the algorithms. They discuss advanced topics such as the behavior of individual particles, global convergence, time complexity, and rate of convergence. The authors also present various examples and applications to show the applicability of QPSO algorithms. In addition, the book includes the source code of the algorithm"--
"A Chapman & Hall book."
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Mathematical optimization; Particles (Nuclear physics); Swarm intelligence; Electronic books